2019
DOI: 10.5614/crbb.2019.1.1/hzra413
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of antioxidant and xanthine oxidase inhibitory activity of Triadica cochinchinensis stem bark

Abstract: Triadica cochinchinensis has been used traditionally to treat diseases related to oxidative stress. Nonetheless, little is known about its biological activity. This study aimed to evaluate the antioxidant and xanthine oxidase inhibitory activity of this plant. For this purpose, qualitative phytochemicals, total phenolic, total flavonoid, antioxidant assays (DPPH and FRAP), and xanthine oxidase assay were evaluated towards methanol and organic fractions of its stem bark. Results showed the occurrence of flavono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…According to our previous study with modifications 5,7 , total phenolics in the ethanol extract and organic fractions of M. scabra fruits were evaluated spectrophotometrically using the Folin-Ciocalteu (FC) method. A linear gallic acid standard curve was first established within a concentration range of 6.25 to 100 µg/mL versus absorbance of molybdenum-tungsten blue complex at 635 nm.…”
Section: Total Phenolics Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…According to our previous study with modifications 5,7 , total phenolics in the ethanol extract and organic fractions of M. scabra fruits were evaluated spectrophotometrically using the Folin-Ciocalteu (FC) method. A linear gallic acid standard curve was first established within a concentration range of 6.25 to 100 µg/mL versus absorbance of molybdenum-tungsten blue complex at 635 nm.…”
Section: Total Phenolics Assaymentioning
confidence: 99%
“…Total flavonoids content in the ethanol extract and organic fractions of M. scabra fruits was evaluated spectrophotometrically using the aluminum chloride method as previously reported with modifications 5,7 . A linear quercetin standard curve was first established within a concentration range of 1.56 to 100 µg/mL versus the absorbance of the yellow complex at 425 nm.…”
Section: Total Flavonoids Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Triadica cochinchinensis is a tree or shrub belonging to the Euphorbiaceae family ( Figure 1 A) and one of the main nectar plants in southern China during summer time, showing a long flowering stage and high nectar production [ 16 , 17 ]. Traditionally used in Chinese herbal medicine, its leaves, bark and roots can be used to treat various internal pathological conditions, including nephritis, oedema, ascites, constipation and dysuria, as well as external pathologies, such as allergic dermatitis, mastitis, bruises, wounds and snakebites [ 18 , 19 ]. Recent studies have shown that T. cochinchinensis leaf and stem parts contain various bioactive compounds, including diterpenoids, phenolics, flavonoids and tannins, which are the main components imparting antioxidant, anti-inflammatory, antibacterial, hepatoprotective and antidiabetic effects [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%